Zebrafish and Medaka as model organisms for climate change research: Global literature scientometric analysis - Nor Azra, Mohamad; Mohd Noor, Mohd Iqbal; Pau Tan, Min; Dawood, Mahmoud; Amin, Muhammad; Zekker, Ivar; Fuad Abdullah, Muhammad; Abd Latif, Zulkiflee; Pardi, Faezah (Frontiers in Earth Science, 2022)
Determining how climate change affects aquatic organisms, such as fish is vital, since this could directly or indirectly impact food and protein sources that are important for human nutrition. Thus, identifying suitable organisms for studying the impacts of climate change on aquatic species is essential. It is most effective to select model organisms for climate change study and determine how each organism might adapt within the diversity of organisms present. This study aimed to review the current development and frontiers of climate change’s model organism based on the literature. We conducted a scientometric analysis by differentiating between publications on different model species, the number and origin of authors and affiliations involved, the citation analysis, and the most common keywords used. Increased publication numbers for Zebrafish and Medaka were detected during the analysis of the networks. Our results showed that both species are among the most important aquatic model organisms for climate change related research. Furthermore, we found that these model organisms, especially the Zebrafish are becoming increasingly important towards climate change related studies, because of their simple anatomy and established biological studies. Our analysis could be on the forefront for disseminating and communicating scientific knowledge and impactful discoveries to researchers, academics, policymakers, and to the public worldwide for future contribution to the community resources preservation.